Produção da cartilha “Doutô, meu filho só come besteira!” para orientação sobre o excesso de peso na adolescência: Booklet production “Doc, my son just eats junk food!” to the adolescence overweight orientation (Health and Biosciences, 2021)
Adolescence is a physical and psychological changing phase, as well as a period when the organism needs energy for development, which leaves this age range vulnerable regarding nutritional risks, especially overweight. This study aimed to present the elaboration of an informative booklet, directed to the teen audience. Data surveys were carried out to corroborate the production relevance, then, for the information collection used in the material, we analyzed scientific articles, institutional documents and website texts. Layout, illustrations, colors, titles, size and format of the text were planned. Subsequently, the booklet was sent for technical and orthographic reviews. Finally, it was sent for the ISBN by the Brazilian Book Chamber registration and for printing copies. The material presented sixteen pages, with 21 x 29.7 cm dimensions. 100 copies were printed in the first edition under the ISBN register: 978-65-00-10004-4. In its content, an informative, critical and reflective approach of aspects that trigger excess weight in adolescents and impact the quality of life of this population were proposed. Therefore, this article presented the process of preparing a booklet aimed at health education in adolescents, but we emphasize the information is synthesized and it is for a quick and playful understanding of the topic, thus not replacing a careful evaluation of a health professional.